2019
DOI: 10.1371/journal.pone.0224019
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in risk factors of lymph node metastasis in patients with early gastric cancer

Abstract: Accurate prediction of lymph node status is of crucial importance in the appropriate treatment planning for patients with early gastric cancer (EGC). Some studies have examined factors predicting lymph node metastasis (LNM) in EGC; however, these studies did not consider sex-specific differences. This study aimed to investigate sex-specific differences in predictive risk factors of LNM in EGC based on surgical specimens. Patients who underwent surgical treatment for EGC between January 2003 and February 2016 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
3
7
1
Order By: Relevance
“…The incidence of male GC is known to be higher than that of female GC, but the mortality rate of female patients with GC is higher than that of male patients ( 15 17 ). In this study, female patients with EGC had a higher LNM ratio than male patients (17.0% vs. 10.4%), which was consistent with previous studies ( 8 , 10 , 25 ). It is therefore necessary to analyze the risk factors for LNM in male and female patients with EGC separately.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of male GC is known to be higher than that of female GC, but the mortality rate of female patients with GC is higher than that of male patients ( 15 17 ). In this study, female patients with EGC had a higher LNM ratio than male patients (17.0% vs. 10.4%), which was consistent with previous studies ( 8 , 10 , 25 ). It is therefore necessary to analyze the risk factors for LNM in male and female patients with EGC separately.…”
Section: Discussionsupporting
confidence: 93%
“…A number of researchers have found that female sex is an independent risk factor for lymph node metastasis in EGC. The estrogen signaling pathway in women affects the generation and development of breast cancer and endometrial cancer; it has also been shown to affect the occurrence and development of gastric cancer [6,29,30]. Our research did not nd that gender affects the lymph node metastasis of EGC.…”
Section: Discussioncontrasting
confidence: 65%
“…Expanded criteria have shown an effort to broaden the scope of endoscopic resection using histologic differentiation, size, presence of ulcers, and depth of submucosal invasion. To date, vague pathological and clinical factors have been mainly used [12][13][14] . Recently, there was a concern that use of expanded criteria may lead to a higher rate of LNM in EGC 13,15 .…”
mentioning
confidence: 99%